Digitalisasi dalam Karawitan Sunda: Kajian Perkembangan Media, Bentuk Penyajian, dan Estetika - Moch Zacky Musyafa; Rengga Ramayuda (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2026)
This study aims to analyse how digital technology reshapes the media, performance forms, and aesthetic values of Sundanese karawitan in contemporary practice. The analysis focuses on three main themes: digital media transformation, hybrid performance forms, and performative aesthetics. Using a narrative review approach, this study synthesises open-access literature published between 2020 and 2025 to examine the influence of digital platforms, remote music production, and online dissemination on the transformation of traditional musical expression. The findings reveal three main transformations. First, digital media expand the functions of documentation, distribution, and interaction, enabling broader access to karawitan. Second, technology-based experimentation gives rise to hybrid performances that integrate Sundanese musical structures with electronic sound processing, virtual instruments, and multisensory stage design. Third, aesthetic experience shifts towards interactive and participatory forms through live responses, digital visualisation, and real-time sound manipulation. Despite these opportunities, challenges emerge in the form of sonic homogenisation and the risk of cultural commodification. This study concludes that Sundanese karawitan creators act as cultural mediators who navigate between traditional values and technological innovation. Strengthening digital literacy, cultural sensitivity, and ethical production practices is essential to sustain the development of karawitan in the digital era.